Serum osteoprotegerin (OPG) measurement in Behcet's disease - Ilhan, Nafiye Fulya; Demir, Nesrin; Demir, Tamer; Godekmerdan, Ahmet (Tubitak Scientific & Technological Research Council Turkey, 2011)
Aim: Recent studies indicate that osteoprotegerin (OPG) acts as an important molecule in the development of vascular diseases. The aim of the present study was to examine the association between serum OPG levels and Behcet's disease (BD). Materials and methods: Twenty-five patients with BD and 20 healthy control subjects, matched for age and sex, were included in this study. Serum levels of OPG were determined using ELISA. Results: We found that serum levels of OPG were significantly higher in patients with BD than in healthy control subjects (813.75 +/- 11 vs. 655.56 +/- 17 pg/mL, P = 0.002). There was no difference between active patients and those in remission. Conclusion: Collectively, serum OPG levels were increased in BD patients, suggesting that OPG might be linked with the development of vasculitis or other inflammatory processes. It was determined that OPG cannot be used as a monitoring test by itself; however, it might be a useful marker for supporting clinical and laboratory findings in relation with BD. Further detailed studies are necessary for a more definitive evaluation of these results.
Behçet hastalar?nda serum osteoprotegerin ölçümü
Keywords: Behcet's disease; osteoprotegerin